Hydration Water Freezing in Single Supported Lipid Bilayers. (5th June 2012) - Toppozini, Laura; Armstrong, Clare L.; Kaye, Martin D.; Tyagi, Madhusudan; Jenkins, Timothy; Rheinstädter, Maikel C.
Abstract : We present a high-temperature and high-energy resolution neutron scattering investigation of hydration water freezing in single supported lipid bilayers. Single supported lipid bilayers provide a well-defined biological interface to study hydration water dynamics and coupling to membrane degrees of freedom. Nanosecond molecular motions of membrane and hydration water were studied in the temperature range 240 K < T < 290 K in slow heating and cooling cycles using coherent and incoherent elastic neutron scattering on a backscattering spectrometer. Several freezing and melting transitions were observed. From the length scale dependence of the elastic scattering, these transitions could be assigned to freezing and melting of hydration water dynamics, diffusive lipid, and lipid acyl-tail dynamics. Coupling was investigated by comparing the different freezing and melting temperatures. While it is often speculated that membrane and hydration water dynamics are strongly coupled, we find that membrane and hydration water dynamics are at least partially decoupled in single bilayers.